Soil Conversation Expertise - Куценко, М. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 1970)
The goals and the tasks of soil-conservation examination of agrolandscapes are specified, the quantitative criteria and the coefficients are proved, which permit to optimize of systems for the measures against erosion. The general algorithm of automated realization of such examination was proposed.